2014
DOI: 10.1371/journal.pone.0084309
|View full text |Cite
|
Sign up to set email alerts
|

A Double Mechanism for the Mesenchymal Stem Cells' Positive Effect on Pancreatic Islets

Abstract: The clinical usability of pancreatic islet transplantation for the treatment of type I diabetes, despite some encouraging results, is currently hampered by the short lifespan of the transplanted tissue. In vivo studies have demonstrated that co-transplantation of Mesenchymal Stem Cells (MSCs) with transplanted pancreatic islets is more effective with respect to pancreatic islets alone in ensuring glycemia control in diabetic rats, but the molecular mechanisms of this action are still unclear.The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 31 publications
4
60
2
3
Order By: Relevance
“…Several different configurations have been used to facilitate islet–MSC interactions during coculture in vitro, including direct contact of islets on an adherent monolayer of MSCs ; the formation of composites by suspension culture of islets and MSCs ; and indirect coculture conditions, where islets and MSCs are physically separated by porous barriers to prevent contact but allow the diffusion of soluble mediators . In agreement with our study, direct contact coculture of islets with MSCs has consistently been reported to improve glucose‐stimulated insulin secretion, whereas noncontact coculture systems are more variable, with some reports of enhanced insulin secretion and others of no effect . There is convincing evidence that at least some of the beneficial effects of MSCs on β‐cell function are mediated via secreted molecules , which should be able to access the islet cells in the indirect coculture systems.…”
Section: Discussionsupporting
confidence: 88%
“…Several different configurations have been used to facilitate islet–MSC interactions during coculture in vitro, including direct contact of islets on an adherent monolayer of MSCs ; the formation of composites by suspension culture of islets and MSCs ; and indirect coculture conditions, where islets and MSCs are physically separated by porous barriers to prevent contact but allow the diffusion of soluble mediators . In agreement with our study, direct contact coculture of islets with MSCs has consistently been reported to improve glucose‐stimulated insulin secretion, whereas noncontact coculture systems are more variable, with some reports of enhanced insulin secretion and others of no effect . There is convincing evidence that at least some of the beneficial effects of MSCs on β‐cell function are mediated via secreted molecules , which should be able to access the islet cells in the indirect coculture systems.…”
Section: Discussionsupporting
confidence: 88%
“…MSCs also secrete a wide range of factors that induce tissue repair and angiogenesis (23); release microvesicles containing microRNAs, lipids, and proteins (24); and act as a stromal cell support system by laying down extracellular matrix (ECM), which may provide a physical niche for transplanted cells (25). Recent studies, including our own (6)(7)(8), have established that MSCs have the capacity to enhance islet function in vitro (4,(9)(10)(11) and have demonstrated that cotransplantation of islets and MSCs into diabetic animals improves islet functional survival and glycemic control (3,5,8,18,(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…A number of MSC-derived trophic factors have been shown to influence the graft niche by modifying the responses of host immune, endothelial, or progenitor cells to reduce inflammatory or immune responses (1,2) and to improve graft revascularization (3)(4)(5). However, we (6)(7)(8) and others (4,(9)(10)(11) have demonstrated that MSCs also have direct effects on donor islet cells to improve their survival and secretory function. Thus, we previously used direct contact coculture of islets with MSCs derived from kidney (6) or adipose tissue (7) to enhance glucose-stimulated insulin secretion (GSIS) in vitro and demonstrated that this results in superior in vivo function for islet-alone grafts at the experimental renal subcapsular (6) and clinically preferred intraportal transplantation site (7).…”
mentioning
confidence: 99%
“…24,27 Hence, islets. [54][55][56] These findings should be validated further to improve our knowledge on the contribution of MSCs to the success of islet transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%